Maternal fasting glucose levels throughout the pregnancy and risk of adverse birth outcomes in newborns: a birth cohort study in Foshan city, Southern China. Issue 1 (13th January 2023) - Yang, Yin; Lin, Qingmei; Ma, Liming; Lai, Zhihan; Xie, Junxing; Zhang, Zilong; Wu, Xueli; Luo, Weidong; Hu, Pengzhen; Wang, Xing; Guo, Xiaoling; Lin, Hualiang
Abstract: Objective: We aimed to investigate the associations between maternal fasting plasma glucose (FPG) levels and glycemic fluctuations during different trimesters and adverse birth outcomes among newborns. Methods: This cohort study used data from 63 213 pregnant women and their offspring in Foshan city from November 2015 to January 2019. Associations between maternal FPG and glycemic fluctuations during different trimesters and adverse birth outcomes [congenital heart defect (CHD), macrosomia, small/large for gestational age (SGA/LGA), and preterm birth (PTB)] in newborns were estimated using mixed-effects logistic regression models. Results: A total of 45 516 participants accepted at least one FPG test throughout pregnancy, and 7852 of whom had glycemic trajectory data. In the adjusted model, higher maternal FPG throughout the pregnancy was associated with an increased risk of adverse birth outcomes (except for SGA). Each 1 mmol/L increase in maternal FPG during trimester 1 was associated with higher odds of CHD (OR = 1.14 (95% CI: 1.02, 1.26)). The same increase in maternal FPG during trimester 3 was associated with a higher risk of PTB (OR = 1.05 (95% CI: 1.01, 1.10)). Increment of maternal FPG during trimester 2 and trimester 3 was associated with a higher risk of macrosomia and LGA. Increase in FPG throughout the pregnancy was associated with slightly lower odds of SGA. Similar results were observed when analyzing the associations between glycemic fluctuations during different trimesters and adverse birth outcomes. Conclusions: Our findings indicate higher maternal FPG levels during different trimesters were associated with different adverse birth outcomes, which suggests the importance of glycemic management throughout the pregnancy.